Skin and hair follicle integrity is crucially dependent on β1 integrin expression on keratinocytes - Brakebusch, Cord (Oxford University Press, 2000)
β1 integrins are ubiquitously expressed receptors that mediate cell–cell and cell–extracellular matrix interactions. To analyze the function of β1 integrin in skin we generated mice with a keratinocyte-restricted deletion of the β1 integrin gene using the cre–loxP system. Mutant mice developed severe hair loss due to a reduced proliferation of hair matrix cells and severe hair follicle abnormalities. Eventually, the malformed hair follicles were removed by infiltrating macrophages. The epidermis of the back skin became hyperthickened, the basal keratinocytes showed reduced expression of α6β4 integrin, and the number of hemidesmosomes decreased. Basement membrane components were atypically deposited and, at least in the case of laminin-5, improperly processed, leading to disruption of the basement membrane and blister formation at the dermal–epidermal junction. In contrast, the integrity of the basement membrane surrounding the β1-deficient hair follicle was not affected. Finally, the dermis became fibrotic. These results demonstrate an important role of β1 integrins in hair follicle morphogenesis, in the processing of basement membrane components, in the maintenance of some, but not all basement membranes, in keratinocyte differentiaton and proliferation, and in the formation and/or maintenance of hemidesmosomes.